MRI characteristics of lumbosacral dural arteriovenous fistulas - Zhu, Jinyu; Zhu, Wangshu; Li, Minghua; Wei, Xiaoer; Chen, Zheyi; Li, Yuehua (Frontiers in Neurology, 2023)
Background and purpose Spinal dural arteriovenous fistulas located in the lumbosacral region are rare and present with nonspecific clinical signs. The purpose of this study was to find out the specific radiologic features of these fistulas. Methods We retrospectively reviewed the clinical and radiological data of 38 patients diagnosed with lumbosacral spinal dural arteriovenous fistulas in our institution from September 2016 to September 2021. All patients underwent time-resolved contrast-enhanced three-dimensional MRA and DSA examinations, and were treated with either endovascular or neurosurgical strategies. Results Most of the patients (89.5%) had motor or sensory disorders in both lower limbs as the first symptoms. On MRA, the dilated filum terminale vein or radicular vein was seen in 23/30 (76.7%) patients with lumbar spinal dural arteriovenous fistulas and 8/8 (100%) patients with sacral spinal dural arteriovenous fistulas. T2W intramedullary abnormally high signal intensity areas were found in all lumbosacral spinal dural arteriovenous fistula patients, with involvement of the conus present in 35/38 (92.1%) patients. The “missing piece sign” in the intramedullary enhancement area was seen in 29/38 (76.3%) patients. Conclusion Dilatation of the filum terminale vein or radicular vein is powerful evidence for diagnosis of lumbosacral spinal dural arteriovenous fistulas, especially for sacral spinal dural arteriovenous fistulas. T2W intramedullary hyperintensity in the thoracic spinal cord and conus, and the missing-piece sign could be indicative of lumbosacral spinal dural arteriovenous fistula.